Essential light chain S195 phosphorylation is required for cardiac adaptation under physical stress - Scheid, Lisa-Mareike; Mosqueira, Matias; Hein, Selina; Kossack, Mandy; Jürgensen, Lonny; Müller, Marion; Meder, Benjamin; Fink, Rainer; Katus, Hugo; Hassel, David (Cardiovascular research, 2016)
AimsRegulatory proteins of the sarcomere are pivotal for normal heart function and when affected by mutations are frequently causing cardiomyopathy. The exact function of these regulatory proteins and how mutations in these translate into distinct cardiomyopathy phenotypes remains poorly understood. Mutations in the essential myosin light chain (ELC) are linked to human cardiomyopathy characterized by a marked variability in disease phenotypes and high incidences of sudden death. Here we studied the role of the highly conserved S195 phosphorylation site of ELC using heterozygous adult zebrafish lazy susan (lazm647) in regulating contractile function in normal physiology and disease.Methods and resultsEchocardiography revealed signs of systolic dysfunction in otherwise phenotypically unremarkable heterozygote mutants. However, after physical stress, heart function of laz heterozygous zebrafish severely deteriorated causing heart failure and sudden death. Mechanistically, we show that upon physical stress, ELCs become phosphorylated and lack of S195 dominant-negatively impairs ELC phosphorylation. In vitro motility analysis with native myosin from adult heterozygous hearts demonstrates that S195 loss, specifically following physical stress, results in altered acto-myosin sliding velocities and myosin binding cooperativity, causing reduced force generation and organ dysfunction.ConclusionUsing adult heterozygous zebrafish, we show that ELC S195 phosphorylation is pivotal for adaptation of cardiac function to augmented physical stress and we provide novel mechanistic insights into the pathogenesis of ELC-linked cardiomyopathy.